A variação da preposição A no emprego dos verbos, visar , assistir e aspirar , no Português Brasileiro escrito - Benício, Marina Ataíde Silveira (2008)
This paper presents a survey conducted as part of a sociolinguistics study on the use of the preposition a , which precedes the object of syntactic structures with the verbs aim, watch and aspire, in written Brazilian Portuguese, with the purpose of analyzing the behavior of that preposition within the use of those verbs, considering the variation and conditioning factors which act in the realization of the variable. The work is based on theoretical assumptions of sociolinguistics proposed by Labov (1972), and studies of Weinreich, Labov and Herzog (2006). The approach used was that of Traditional Grammar, based on Cunha (1999), Cegalla (1999), Rocha Lima (1978) and Bechara (2001), and in some studies in generativism, proposed by Chomsky, based on Morais (1999), Oliveira (1999), Ramos (1992) and Stowell (1981). The corpus of 734 data was collected from four newspapers in Brazil: O Globo, Folha de São Paulo, Estado de Minas and O Estado de São Paulo.The analysis showed the rate of change in the distribution of the preposition in newspapers, as well as frequencies and percentages of change with respect to the conditioning factors. Based on statistical results, some assumptions could be proved: the adjacency of the complemention, the infinitive, pronoun, and clitic accusative; and pronominal PRO favors the absent of the preposition.